2018
DOI: 10.1007/s10699-018-9547-1
|View full text |Cite
|
Sign up to set email alerts
|

The Heart of an Image: Quantum Superposition and Entanglement in Visual Perception

Abstract: We analyse the way in which the principle that 'the whole is greater than the sum of its parts' manifests itself with phenomena of visual perception. For this investigation we use insights and techniques coming from quantum cognition, and more specifically we are inspired by the correspondence of this principle with the phenomenon of the conjunction effect in human cognition. We identify entities of meaning within artefacts of visual perception and rely on how such entities are modelled for corpuses of texts s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 42 publications
(63 reference statements)
1
25
0
Order By: Relevance
“…This means that the interactions between 'words', which are the boson particles of language in our description, is mainly one of 'quantum superposition' and 'quantum entanglement', or more precisely one of 'overlapping de Broglie wave functions'. This corresponds well with some of our earlier findings, when studying the combinations of concepts in human language, namely that superposition and entanglement are abundant, and the type of entanglement is deep, namely it also violates additionally to Bell's inequality the marginal laws (Aerts, 2009b;Aerts, Broekaert & Gabora, 2011;Aerts & Sozzo, 2011Aerts, Sozzo & Veloz, 2015aAerts et al, 2012Aerts et al, , 2018aAerts et al, ,b,c, 2019aAerts Arguëlles, 2018;Beltran & Geriente, 2019).…”
Section: Introductionsupporting
confidence: 91%
“…This means that the interactions between 'words', which are the boson particles of language in our description, is mainly one of 'quantum superposition' and 'quantum entanglement', or more precisely one of 'overlapping de Broglie wave functions'. This corresponds well with some of our earlier findings, when studying the combinations of concepts in human language, namely that superposition and entanglement are abundant, and the type of entanglement is deep, namely it also violates additionally to Bell's inequality the marginal laws (Aerts, 2009b;Aerts, Broekaert & Gabora, 2011;Aerts & Sozzo, 2011Aerts, Sozzo & Veloz, 2015aAerts et al, 2012Aerts et al, , 2018aAerts et al, ,b,c, 2019aAerts Arguëlles, 2018;Beltran & Geriente, 2019).…”
Section: Introductionsupporting
confidence: 91%
“…Quantum entanglement in human language was studied within the Brussels approach [1] to quantum cognition [2,3,4,5,6,7,8,9,10,11,12,13,14] by means of psychological experiments on human participants about the way language is used by them, and several aspects of it were researched [15,16,17,18,19]. In the present article we will investigate how quantum entanglement appears in corpuses of documents.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of entanglement in human cognition have been studied in our group in the past [ 28 , 29 , 30 , 62 , 63 , 64 , 65 , 66 ], and we want to bring forward an analysis here that will bring us to the second new insight of this article. Let us briefly review how we showed that the combination of two concepts spontaneously makes ‘entanglement’ emerge, such that it can be illustrated in a simple way that it is a quantum entanglement where Bell’s inequalities are violated.…”
Section: Entropy and Puritymentioning
confidence: 99%
“…We have named these studies ‘The Google Books Natural Language Processing Study’ and ‘The COCA Natural Language Processing Study’ in Table 2 . In the fifth study in Table 2 , images from ‘Google Images’ were examined for the occurrence of the various images of The Horse Growls , The Horse Whinnies , The Bear Growls , or The Bear Whinnies , respectively, and the statistics generated by this were used to calculate the probabilities needed to fill the terms of the Clauser–Horne–Shimony–Holt inequalities [ 30 ].…”
Section: Entropy and Puritymentioning
confidence: 99%
See 1 more Smart Citation